Toksisitas Ekstrak Terpurifikasi dengan N-heksan Buah Kecubung (Datura metel L.) terhadap Mortalitas Larva Nyamuk Aedes aegypti - Aditya Rico Armyandi; Dwi Wahyuni; Kamalia Fikri (saintifika, 2022)
Infectious diseases caused by animal vectors are currently still a health problem in the world even in Indonesia, especially the Aedes aegypti mosquito which is the vector for the spread of dengue fever. Chemical control is still a priority for the community, such as the use of abate. Continuous use of abate can cause resistance to the Aedes aegypti mosquito to the next generation and pollute water conditions. One of the control solutions can be done with natural insecticides such as amethyst fruit (Datura metel L.). The purpose of making purified extracts is to remove unnecessary impurities and get a larger content of active compounds and increase the concentration of active compounds. The concentration of amethyst extract (Datura metel L.) used was a concentration of 100 ppm, 500 ppm, 1000 ppm, 1500 ppm, 1gr abate as a positive control and aquades as a negative control. The amount of Lethal Concentration-50 (LC50) purified extract of amethyst fruit (Datura metel L.) with n-hexane was 494.987 ppm. The active compound content of amethyst fruit (Datura metel L.) in the n-hexane fraction after a phytochemical screening test was carried out was positive for alkaloids, steroids, terpenoids and tannins. The toxicity of the purified extract with n-hexane of amethyst (Datura metel L.) against Aedes aegypti mosquito larvae within 24 hours is considered toxic because it has an LC50 value of less than 1000 ppm.